Competitive Advantage Between Indonesia and Thailand on Electric Vehicle Manufacturing - Anggara Raharyo; Gita Ardynmas Mertawan; Riski Baskoro (Journal of Economics and Business Aseanomics (JEBA), 2022)
Indonesia and Thailand engage in the competition of Foreign Direct Investment (FDI) for Electric Vehicle (EV) industry. This study aims to identify determinant factor of FDI in EV industry, analyse the strategy to attract FDI, and see the competitiveness between Indonesia and Thailand in EV manufacturing. Qualitative method used by comparing Indonesia and Thailand through Porter Diamond Model. The model consists of four parts such as factor of conditions; demand conditions; related and supporting business; firm strategy, structure, and rivalry. There are 14 variables inside the four parts to analyse both countries competitiveness through comparing them in every variable. Results indicate that Indonesia has 5 out of 14 variables better Thailand while Thailand has 9 out of 14 variables that is better than Indonesia. Indonesia has the advantage on consumer side due to the possible lower price of EV while Thailand has the advantage on production activities